Web Services Feature Interaction Detection Based on Situation Calculus - Jiuyun Xu; Wengong Yu; Kun Chen; Reiff-Marganiec, S (2010 6th World Congress on Services, 2010)
Feature interaction has been identified as a problem in the telecommunications domain in the 1980s, but since it has been shown to be a problem of systems that are composed of individually designed components. Clearly Web service composition is a way of building services from independently designed components and hence is subject to the same problem. This paper investigates the detection of feature interactions in Web services at runtime and proposes a novel detection method by taking inspiration from the Situation Calculus. Two case studies show that it is effective for detecting feature interactions in composite Web services.